2019
DOI: 10.2217/nnm-2019-0253
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Comparison of the Biodistribution and long-term Fate of Colloids – Gold Nanoprisms and Nanorods – With Minimum Surface Modification

Abstract: Aim: To study the difference in biodistribution of gold nanoprisms (NPr) and nanorods (NR), PEGylated to ensure colloidal stability. Materials & methods: Surface changes were studied for nanoparticles in different media, while the biodistribution was quantified and imaged in vivo. Results: Upon interaction with the mouse serum, NR showed more abrupt changes in surface properties than NPr. In the in vivo tests, while NPr accumulated similarly in the spleen and liver, NR showed much higher gold presence in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…After sequestration in the liver and spleen, AuNPs-PAA-Ctxb showed a long-term retention, with their concentration significantly decreasing only after 6 months. This indicates a slow elimination process, which has also been reported by several other long-term biodistribution studies [21,25,[55][56][57]. In addition, it was reported that negatively charged particles were retained for slightly longer in the liver and spleen, and were eliminated more slowly compared to positively or neutrally charged particles [25,51].…”
Section: Daems Et Alsupporting
confidence: 72%
See 2 more Smart Citations
“…After sequestration in the liver and spleen, AuNPs-PAA-Ctxb showed a long-term retention, with their concentration significantly decreasing only after 6 months. This indicates a slow elimination process, which has also been reported by several other long-term biodistribution studies [21,25,[55][56][57]. In addition, it was reported that negatively charged particles were retained for slightly longer in the liver and spleen, and were eliminated more slowly compared to positively or neutrally charged particles [25,51].…”
Section: Daems Et Alsupporting
confidence: 72%
“…Interestingly, although 97% of the injected AuNPs-PAA-Ctxb were cleared from the blood after 6 h, an increasing trend in gold concentration was observed in the liver and spleen for up to 72 h post-injection. Comparable results were obtained with PEGylated AuNPs of different sizes (6.2 nm-61.2 nm) or with different shapes (rods and triangles) reaching maximum gold concentrations in the liver and spleen between 24 h and 6 days post-injection [54,55]. This increase could potentially be attributed to a gradual redistribution of AuNPs-PAA-Ctxb from other tissues to the liver and spleen [22].…”
Section: Daems Et Almentioning
confidence: 74%
See 1 more Smart Citation
“…This amount was comparable to results obtained by other methods. [35][36][37] Results of the current study showed that GNRs were not toxic to the cells below 10 14 NR/mL (P > .05). Previous studies also demonstrated no significant differences in functional capacity (viability, proliferation, and differentiation) between unlabelled and GRNs-labelled cells.…”
Section: Discussionmentioning
confidence: 55%
“…It was found that among different types of AuNPs (such as nanorods, nanostars, and nanocubes), Au nanoprisms (AuNPrs) possess the highest photothermal conversion efficiency [ 42 , 43 ], and are easily internalized in the cells compared to AuNRs [ 44 ]. In addition, AuNPrs are beneficial for long-term biosafety as they can be removed from the tissue faster than smaller AuNRs [ 45 ].…”
Section: Introductionmentioning
confidence: 99%